Sanitation and Hygienic Practices of Ready-to-Drink Milk Seller Based on Total of Coliform and Staphylococcus aureus - Pisestyani, Herwin; Ramadhani, Nada Nursaffana; Sudarwanto, Mirnawati; Lukman, Denny Widaya; Wicaksono, Ardilasunu (Jurnal Medik Veteriner, 2021)
Dairy products are innovative to improve the economic value of milk. Poor attention to the importance of good hygiene and milk handling of milk can lead to microbial contamination of milk, such as coliform and Staphylococcus aureus. This study aimed were to define the safety of ready-to-drink milk which sold around Dramaga and Cilibende IPB University campuses based on the total coliform and S. aureus and to determine the factors that affected it. Data were obtained by questionnaire from 12 sellers, furthermore milk samples were taken from 13 ready-to-drink milk's sellers with 3 replication The data were presented descriptively and analyzed using chi-square test to determine the relationship between the practice of the sellers with total contamination of coliform and S. aureus. The data results were compared with SNI 01-7388-2009 concerning the Maximum Limits of Microbial Contamination in Food. The average of coliform contamination in Dramaga and Cilibende 5,92í—103 ± 9,28í—103 CFU/ml and 7,60í—104 ± 1,25í—105 CFU/ml, respectively. The average of S. aureus contamination in Dramaga and Cilibende 3,84í—102 CFU/ml ± 5,36í—102 and 8,44í—104 ± 1,96í—105 CFU/ml, respectively. Furthermore, several practices of ready-to-drink milk sellers had a significant relationship with coliform contamination (p<0.05), which were the table cleanliness (p=0.020), distance to the crowd (p=0.001), and hand washing (p=0.001). The practice of ready-to-drink milk sellers had a significant relationship with S. aureus contamination (p<0.05) which were the table cleanliness (p=0.020), and distance of the crowd (p=0.020). The high contamination by coliform and S. aureus is caused by the poor sanitation and personal hygiene of the milk seller during the serving and processing of the milk.